Information systems : failure analysis - NATO Advanced Research Workshop on Failure Analysis of Information Systems (1986 :cBad Windsheim, Federal Republic of Germany); Wise, John A.; Debons, Anthony (Berlin : Springer-Verlag, 1987)
41